Modern electronic media and the arab spring – 2011 - Myamesheva, G.; Davydova, I. (Journal of Oriental Studies, 2016)
In the informational society era the role of information is growing quickly. Modern media have a wide diapason and spectrum ofactivity. In the context of globalization the media turns into the fi rst power instead of the fourth. Modern media is not only to inform, butalso to entertain and shape public opinion. . The Internet creates a special media environment, which is similar to television, radioand print media. Features of the electronic media: constant audience, media effi ciency (regularly updating websites, instant access toinformation), constant feedback from the audience (forums, voting, polls, conferences, guestbook). Social media are widely used inpolitical life of different countries, both from politicians’ side and other subjects of political activity. First of all, these subjects are educatedyoung people, knowing the high-tech technologies. Under this scenario happened the events of the Arab spring of 2011 .